Towards a phenomenologically oriented couple psychotherapy. (Phenomenology, Humanities and Sciences, 2023)
The present theoretical research work intends, in the first place, to critically address the implications of exercising couples psychotherapy from a substantialist ontology, typical of the natural sciences, when its categories are put at the service of unveiling the human. It is exposed that dealing with human experience executed in this way tends to generate the imposition of an ideal type of functioning, hiding the mobility of the loving phenomenon, which obstructs access to the singularity of the experience of being together with others and ends up regulating and explaining it through a comparative exercise with respect to an imposed ideal. Secondly, it seeks to outline the foundations to propose a Phenomenologically Oriented Couples Therapy. Faced with the aforementioned reduction in mobility and uniqueness of the love experience, it is proposed to address the coupling phenomenon from the categories presented by hermeneutic phenomenology, with the purpose of comprehensively revealing the experience of being together with one another. And from that, to formalize a couple psychotherapeutic approach that goes beyond the descriptive and/or explanatory developments typical of the natural sciences.
Keywords: Couples psychotherapy; Hermeneutic phenomenology; Phenomenological psychotherapy